Dual Based Assessment in Improving the Quality of Skills at the Center of Excellence Vocational School - Suwandi, Suwandi; Hanafiah, Hanafiah; Iriantara, Yosal; Sulastini, Rita (CV. Inara, 2022)
This research is motivated by various problems related to the quality and relevance of Indonesian education which are the main issues. Indicators of quality education are marked by graduates who have superior competencies and are able to compete in the business world and industry for graduates from Vocational Secondary Education. Quality vocational education applying quality standards can contribute to the country's economic development, but it still cannot be realized optimally at the time of its implementation. Such conditions occur in SMK graduates in Indonesia so that the open unemployment of SMK graduates is getting bigger. It is interesting to do further research to find out why and how this happened and find solutions to the problems faced. Dual Based Assessment (DuBA) on the vocational skills aspect is expected to be a solution in ensuring the quality of skills at the Center of Excellence Vocational High School and Vocational Schools in general. In particular, this study describes and analyzes the